Acute Uveitis following COVID-19 Vaccination - ElSheikh, Reem H.; Haseeb, Abid; Eleiwa, Taher K.; Elhusseiny, Abdelrahman M. (Ocular immunology and inflammation, 2021)
To describe a case of juvenile idiopathic arthritis (JIA)-associated anterior uveitis after receiving the Sinopharm COVID-19 vaccine. A retrospective case report. An 18-year-old girl, with a history of antinuclear antibody positive oligoarticular JIA, presented with bilateral anterior uveitis 5 days after the second dose of the Sinopharm COVID-19 vaccine. Ocular examination revealed anterior uveitis with reduced visual acuity in both eyes. Anterior segment optical coherence tomography showed hyperreflective dots in the anterior chamber (AC) and fine endothelial granularities representing the circulating cells in the AC. Uveitis in both eyes resolved gradually after topical steroid treatment without recurrence. This report demonstrates a potential causal association of COVID-19 vaccine with anterior uveitis.